Upaya Peningkatan Hasil Belajar Lompat Jauh Melalui Pendekatan Bermain Lompat Tali pada Siswa Kelas IV Sekolah Dasar - Warsiyanti, Y. (Universitas Sebelas Maret, 2018)
Abstract. The students' long jump learning outcomes still do not meet the KKM. This study aims to describe the process of improving long jump learning outcomes through the rope jumping approach to fourth grade students of Katekan 2 Elementary School in Gantiwarno District, Klaten Regency. This research is a classroom action research. The subjects in this study were grade IV students of SDN 2 Katekan in Gantiwarno District, Klaten Regency with a total of 20 students. The instrument used was a long jump performance test. The data analysistechnique used in this study is descriptive qualitative and quantitative. Based on the results of the study, it can be concluded that the effort to increase the results of the long jump through rope jumping in the fourth grade students of Katekan Elementary School 2 of Gantiwarno Subdistrict, Klaten Regency was successfully marked by an increase in the average value of students. The average value of students in pre-action activities was 55.94 with a percentage of completeness of 40%. This condition experienced an increase in the average value of studentsin the first cycle, namely to be equal to 65.63 and the percentage of completeness by 60%. However, this increase has not yet reached the target set previously. Then after proceeding to the second cycle the students' long jump average value increased to 70.50 with the percentage of completeness of 90%. This shows that the previously set target has been reached so that the research is stopped in cycle II. The long jump learning process using the play approach takes place dynamically and pleasantly. Students actively carry out the task and observe the movement of the long jump technique and discuss each other with friends. All aspects ofassessment are mastered by students. The students' long jump ability increases with the markedby all KKM complete students (Minimum Completion Criteria), namely 67.